1973
DOI: 10.1172/jci107509
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Distal Tubule and Cortical Collecting Duct to Vasopressin in the Rat

Abstract: A B S T R A C T Renal micropuncture observations in the rat suggest that the entire "distal tubule" (defined by the micropuncturist as that portion of the renal tubule extending between the macula densa and its first junction with another (renal tubule) may be responsive to vasopressin. However, this portion of the renal tubule contains two segments that are morphologically dissimilar. The "early" distal tubule is lined by epithelium characteristic of the distal convoluted tubule, while the "late" distal tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(66 citation statements)
references
References 16 publications
5
61
0
Order By: Relevance
“…The lack of a clear delineation between each segment of the distal nephron supports previous descriptions of a gradual transition and mixing of tubular segments in the distal nephron of rat, mouse and human ( Figure 6E). [37][38][39][40] The connecting tubule therefore represents a hybrid segment composed of elements from the adjacent metanephric mesenchyme-derived distal tubule and ureteric budderived CD, with the latter nephron segment the mostly likely source of ICs.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a clear delineation between each segment of the distal nephron supports previous descriptions of a gradual transition and mixing of tubular segments in the distal nephron of rat, mouse and human ( Figure 6E). [37][38][39][40] The connecting tubule therefore represents a hybrid segment composed of elements from the adjacent metanephric mesenchyme-derived distal tubule and ureteric budderived CD, with the latter nephron segment the mostly likely source of ICs.…”
Section: Discussionmentioning
confidence: 99%
“…and [Nab, are the bath and collected fluid concentrations of sodium, respectively. previous micropuncture studies (31). The finding by Woodhall and Tisher (31) of a marked heterogeneity in the cellular composition of the subcapsular tubules available for distal micropuncture makes the interpretation of previous studies problematic.…”
Section: Methodsmentioning
confidence: 98%
“…The epithelium lining tubules just before the junction of one "distal" segment with another, usually referred to in micropuncture studies as the "late distal tubule," was found in all cases to consist of epithelium of the cortical collecting tubule (CCT). ' In the Wistar rat, 48.3% of available tubules were of true distal epithelial type, 45% were collecting tubules, and 6.7% were transition zones (31). Thus, it is clear that many of the previous micropuncture results have 1Abbreviations used in this paper: ADH, antidiuretic hormone; CCT, cortical collecting tubule; DCT, distal convoluted tubule; DOCA, deoxycorticosterone acetate; PD, potential difference.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The height of kidney tubule cells is often determined as the mean caliper height, the linear distance between the luminal and basolateral membranes on thin sections (8,10,17). This approach is complicated by at least three kinds of problems.…”
Section: Appendixmentioning
confidence: 99%